DAO Research Trends: Reflections and Learnings from the First European DAO Workshop (DAWO) - Michael Lustenberger; Florian Spychiger; Lukas Küng; Eleonóra Bassi; Sabrina Wollenschläger (Applied Sciences)
Decentralized Autonomous Organizations (DAOs) represent a transformative shift in organizational structures, combining decentralized governance with blockchain-based smart contracts. While DAOs present significant opportunities for innovation, they are confronted with several unresolved challenges, such as the centralization of power, the design of effective governance mechanisms, and the legal uncertainties surrounding their operation. Drawing on insights from recent studies and discussions presented in July 2024 at DAWO24, the first European DAO Workshop, this article explores these issues. The purpose of this article is to identify and analyze the critical research streams in DAO studies, particularly in governance mechanisms, technical frameworks, value assessment, and legal dimensions. A systematic approach, following the PRISMA methodology, was employed to analyze contributions from 14 extended abstracts and 11 full papers presented at DAWO24. The findings highlight the need for more equitable governance structures, secure and scalable technical frameworks, standardized tools for assessing DAOs’ value, and coherent legal frameworks to support decentralized operations. The article concludes by outlining future research directions, urging interdisciplinary collaboration to address current gaps and optimize DAO design, operation, and regulation.